2020
DOI: 10.1088/1361-6544/ab5921
|View full text |Cite
|
Sign up to set email alerts
|

Persistent heterodimensional cycles in periodic perturbations of Lorenz-like attractors

Abstract: We prove that heterodimensional cycles can be created by unfolding a pair of homoclinic tangencies in a certain class of C r -diffeomorphisms (r = 3, . . . , ∞, ω). This implies the existence of a C 2 -open domain in the space of dynamical systems with a certain type of symmetry where systems with heterodimensional cycles are dense in C r . In particular, we describe a class of three-dimensional flows with a Lorenz-like attractor such that an arbitrarily small time-periodic perturbation of any such flow can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…In a series of papers [25][26][27] we have shown that heterodimensional cycles can be a part of a pseudohyperbolic chain-transitive attractor which appears in systems with Shilnikov loops [18,32,38] or after a periodic perturbation of the Lorenz attractor [39]. It follows from our results in the current paper that the attractor in such systems remains heterodimensional for an open set of parameter values.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…In a series of papers [25][26][27] we have shown that heterodimensional cycles can be a part of a pseudohyperbolic chain-transitive attractor which appears in systems with Shilnikov loops [18,32,38] or after a periodic perturbation of the Lorenz attractor [39]. It follows from our results in the current paper that the attractor in such systems remains heterodimensional for an open set of parameter values.…”
Section: Introductionsupporting
confidence: 60%
“…By construction, these estimates are uniform for all systems C 2 -close to f , and when the system is at least C 3 -smooth, the same estimates are also true for the first derivatives with respect to parameters ε. We note also that in the coordinates (27) we have the local stable manifold of O 1 and the image of the local unstable manifold of O 2 straightened:…”
Section: First-return Mapsmentioning
confidence: 99%
“…In the codimension one case we can obtain additional conclusions, compare with [35,Lemmas 11 and 12]. Lemma 5.4.…”
Section: Unfolding the Homoclinic Tangencymentioning
confidence: 58%
“…Next lemma about expansion of volume of local submanifolds tangent to the cone field C cu in Remark 4.1 by the return maps R k is a variation of [35,Lemma 5]. To state it recall the definition of J P = J P (f ) in (1.2) and that a submanifold S is tangent to C cu if T X S ⊂ C cu (X) for every X ∈ S. Proof.…”
Section: Expansion Of Volumementioning
confidence: 99%
See 1 more Smart Citation